2018
DOI: 10.5194/acp-18-16631-2018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variations of aerosols over China from two decades of multi-satellite observations – Part 2: AOD time series for 1995–2017 combined from ATSR ADV and MODIS C6.1 and AOD tendency estimations

Abstract: Abstract. Understanding long-term variations in aerosol loading is essential for evaluating the health and climate effects of airborne particulates as well as the effectiveness of pollution control policies. The expected satellite lifetime is about 10 to 15 years. Therefore, to study the variations of atmospheric constituents over longer periods information from different satellites must be utilized. Here we introduce a method to construct a combined annual and seasonal long time series of AOD at 550 nm using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 58 publications
4
57
0
Order By: Relevance
“…Alfaro-Contreras et al (2017) analyzed several satellite retrievals of AOD for total aerosol and found no consistent trend in coastal China (−0.035, +0.001, −0.010 per decade for MODIS Aqua, MODIS Terra, and MISR, respectively). Sogacheva et al (2018) combined AOD data from the Along-Track Scanning Radiometer (ATSR) and MODIS and found that AOD across China increased significantly from 1995 to 2006 but decreased gradually between 2011 and 2017, which reflects the increased emissions due to rapid economic development and the decreased emissions due to effective emission control regulations. For com-parison, the CAM5 simulations show no statistically significant trend.…”
Section: Non-monotonic Trends Of τ C In East Asian Outflowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfaro-Contreras et al (2017) analyzed several satellite retrievals of AOD for total aerosol and found no consistent trend in coastal China (−0.035, +0.001, −0.010 per decade for MODIS Aqua, MODIS Terra, and MISR, respectively). Sogacheva et al (2018) combined AOD data from the Along-Track Scanning Radiometer (ATSR) and MODIS and found that AOD across China increased significantly from 1995 to 2006 but decreased gradually between 2011 and 2017, which reflects the increased emissions due to rapid economic development and the decreased emissions due to effective emission control regulations. For com-parison, the CAM5 simulations show no statistically significant trend.…”
Section: Non-monotonic Trends Of τ C In East Asian Outflowsmentioning
confidence: 99%
“…Our results are also consistent with trends of dust emissions over East Asia and China in particular as documented in the literature. For example, Song et al (2016) showed that the spring dust storm frequency in arid and semiarid regions of China has decreased by 15.45 storms per year on average over the period of 1982 to 2007. Fan et al (2014) showed that the decrease in springtime dust storms in Inner Mongolia, northern China, from 1982 to 2008 was correlated with advanced vegetation growth, with 1 d earlier green-up data corresponding to a 3 % decrease in spring dust storms.…”
Section: Interannual Variability In Smoke-or Dust-dominated Outflowsmentioning
confidence: 99%
“…Thus, despite the spatial inconsistency, the substantial variability of SO2 and NOx in central China can cause a considerable contribution to overall variations of overall aerosol loading. Spatial mean of aerosol loading is usually used to evaluate variations of regional emission levels [34]. The annual average of MODIS AOD values within Hubei province during 2005-2017 are shown in Figure 10.…”
Section: Spatial and Temporal Distribution Of Particle Pollution In 2mentioning
confidence: 99%
“…Major problems in the retrieval of AOD from satellite observations are the effective decoupling of atmospheric and surface effects on the reflectance measured at the TOA, cloud detection, and the description of the aerosol properties. In the ADL algorithm a cloud mask is applied based on the clouds from AVHRR (CLAVR, Stowe et al, 1991Stowe et al, , 1999, and in the retrieval six aerosol types are used as proposed by Govaerts (2010). For cloud-free pixels, and after application of gas absorption corrections as described in Xue et al (2017), the land surface reflectance in the AVHRR channel 1 (0.64 µm) is parameterised in terms of the measured reflectance in channel 3 (3.75 µm), with coefficients which are functions of the NDVI and scattering angle.…”
Section: Avhrrmentioning
confidence: 99%